El Caribe holandés El colonialismo y sus legados transatlánticos - Oostindie, Gert (Editorial José Marti, 2014)
"Paradise Overseas" presents a tour around the main themes of Dutch Caribbean history and its contemporary legacies. Drawing on wide expertise in Caribbean and Latin American studies, Gert Oostindie strongly posits a refreshing analysis of the Dutch Caribbean in a comparative framework which will be of interest to historians, anthropologists and political scientists alike. Rather than aiming at a comprehensive narrative, he offers a thematic discussion of topics such as the contrasts between Dutch colonization in the Americas and Asia; African slavery, Asian indentured labour and the shaping of plural societies in the Dutch Caribbean; the major contrasts between and within the six Antillean islands and Suriname; the different trajectories of decolonisation and their subsequent costs and benefits; and the changing significance of ethnicity and national identity both in the Dutch Caribbean and its diaspora.